Response To External Forces Driving Quality In Malaysia By Established Local Private Higher Educational Institutions - Dass, Asha B. (2011)
This study is conceptualised based on Seymour’s (1993) contention that quality in any institution or organisation is usually driven by the external forces of accountability, competition, cost and service orientation. This study describes how these external forces identified by Seymour (1993) are driving quality in the context of private higher education in Malaysia.